Fast Matrix Covering in All Programmable Systems-on-Chip - Sklyarov, V.; Skliarova, I.; Rjabov, A.; Sudnitson, A. (Elektronika ir Elektrotechnika, 2014)
The paper suggests a technique for solving the matrix/set covering problem in all programmable systems-on-chip. A novel very fast hardware accelerator is proposed and implemented in the programmable logic (PL) of a Xilinx Zynq microchip. The accelerator is managed by software running in the processing system (ARM Cortex-A9) available on the same microchip and communicating with the PL through high-speed interfaces. The results of implementation, experiments, and comparisons demonstrate significant speedup comparing to software running in general-purpose PC and in the ARM. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7116